Evaluations on the Properties of Polymer and Nanomaterials Modified Bitumen Under Different Aging Conditions - Shaban Ismael Albrka Ali; Khalifa Salem Gallouz; Ikenna D. Uwanuakwa; Mustafa Alas; Mohd Rosli Mohd Hasan (Nanomaterials)
This research evaluates the rheological and mechanical properties of polymer- and nanomaterials-modified bitumen by incorporating nanosilica (NSA), nanoclay (NCY), and Acrylonitrile Styrene Acrylate (ASA) at 5% by weight of the bitumen. The samples were prepared at 165 °C for one hour to obtain homogeneous blends. All samples were subjected to short- and long-term aging to simulate the effects of different operating conditions. The research conducted a series of tests, including consistency, frequency sweep, and multiple creep stress and recovery (MSCR) using the dynamic shear rheometer (DSR) and bending beam rheometer (BBR). The results showed that all modified bitumen outperformed the neat bitumen. The frequency sweep showed a higher complex modulus (G*) and lower phase angle (δ), indicating enhanced viscoelastic properties and, thus, higher resistance to permanent deformation. The BBR test revealed that the bitumen modified with NCY5% has a creep stiffness of 47.13 MPa, a 51.5% improvement compared to the neat bitumen, while the NSA5% has the highest m-value, a 28.5% enhancement compared with the neat bitumen. The MSCR showed that the modified blends have better recovery properties and, therefore, better resistance to permanent deformation under repeated loadings. The aging index demonstrated that the modified bitumen is less vulnerable to aging and maintains their good flexibility and resistance to permanent deformations. Finally, these results showed that adding 5% polymer and nanomaterials improved the bitumen’s’ performance before and after aging by reducing permanent deformation and enhancing crack resistance at low temperatures, thus extending the pavement service life and making them an effective alternative for improving pavement performance in various climatic conditions and under high traffic loads.